Effects of variations of environmental factors and algal bloom on fish larvae in Southern central Vietnam - Quang, Vo Van; Hai, Doan Nhu; Lam, Nguyen Ngoc (Academia Journal of Biology, 2017)
A multivariate analysis was conducted to assess the impact of variations of environmental factors such as temperature, salinity, dissolved oxygen (DO), total suspended solid (TSS), nitrite (NO2-N), nitrate (NO3-N), ammonium (NH3,4-N), phosphate (PO4-P), and silicate (SiO3-Si) concentrations, chlorophyll (chlor) and algal bloom on natural fish larvae in Binh Thuan waters, Vietnam. Temporal and spatial variations of environmental factors were correlated with the abundance and diversity of fish larvae. The abundance and diversity of fish larvae decreased at the sites of the algal blooms. Five environmental factors - temperature, salinity, nitrite, phosphate and silicates - showed a statistically significant impact on the fish larvae, but other factors showed weaker and statistically not significant effects. In the months of algal blooms, phosphate, silicate, nitrite, nitrate, ammonium and salinity influenced blooms substantially, while the effects of temperature were mainly confined to the months without blooms of algae. Algal blooms were lethal to fish larvae and juveniles leading to a decline in their abundance and diversity. This will affect and restrict the process of recruitment of fish stocks in the region. Received 19 December 2016, accepted 30 December 2016